Revitalization of Po Pado: Explaining the Meaning of Educational Value of Oral Tradition In the People of Rakalaba Village, West Golewa District, Ngada Regency - C. Age, Maria Yulita (Syntax Literate, 2021)
This study aims to find and describe the meaning of educational values in Pop Pado in the people of Rakalaba village, West Golewa District, Ngada Regency. This study used a qualitative approach. The results of the study proved that Po Pado in the people of Rakalaba Village, West Golewa District, Ngada Regency is in the form of an old poem, namely a proverb. The meaning of educational value of Po Pado are (1) the meaning of togetherness, (2) the meaning of leluri, (3) the meaning of kinship, (4) the meaning of economy. While the functions of Po Pado's Educational Values are (1) personal functions, (2) family functions, (3) social functions, (4) economic functions, and (5) leadership functions